Alteration of vascular response to norepinephrine, calcitonin gene-related peptide, and acetylcholine in orchidectomized rats. - WANG Wang; SUN Chao; WANG Xian (Acta Pharmacologica Sinica, 2016)
AIM: To determine the long-term effects of orchidectomy on vasoreactivity. METHODS: Orchidectomized rats with or without hormone replacement were raised 1, 2, and 4 months. Vascular responses to norepinephrine, calcitonin gene-related peptide (CGRP), and acetylcholine were tested on three different arteries (thoracic aorta, pulmonary artery, and caudal artery) by functional experiments. RESULTS: Responses to norepinephrine, CGRP, and acetylcholine were not changed by 1 or 2 months deprivation of androgen. In aorta, the dose-response curve of CGRP was shifted to the left by 1 month of testosterone replacement. Response to norepinephrine was increased 4 months after orchidectomy and reversed by testosterone replacement in thoracic aorta. Orchidectomy did not affect CGRP- and acetylcholine-induced relaxation in all the arteries 4 months after orchidectomy. CONCLUSION: Compared to estrogen, the protective effects of androgen on vasoresponsiveness may be through inhibiting vasoconstriction, but is relatively weak.